Integrating logics in the governance of emerging technologies : the case of nanotechnology - Anderson, Derrick Mason; Whitford, Andrew B. (Cambridge : Cambridge University Press, 2021)
The governance of emerging technologies does not follow a single governance paradigm because of complex interactions between government, industry, and civil actors. In this Element, we will argue that for emerging technologies, governance is a 'convergent paradigm'. We introduce governance issues associated with emerging technologies generally before turning to the specifics of nanotechnology. We then approach governance theory and practice by considering different perspectives on governance by their different orientations with respect to object and process. Finally, we construct a matrix of object and process oriented governance activities observed in the case of nanotechnology in the United States.
Title from publisher's bibliographic system (viewed on 30 Mar 2021).
Keywords: Technological innovations -- Management; Technological innovations -- Government policy; Nanotechnology -- Management; Nanotechnology -- Government policy